A retórica erística no júri popular e a soberania do veredicto de um tribunal não técnico: um paradoxo para reflexão - Barros, Clésia dos Santos (2021)
he objective of this study is to reflect on the pros and cons of the sovereignty of the verdicts of the sentencing council of the jury court, which is usually composed of lay people without technical and legal training, to establish a conviction or acquittal and the impacts caused by this form of trial. It is evident, according to the understanding of some jurists, that these jurors, because they are laymen on criminal and procedural matters, may cause losses to the accused, especially in view of the possibility of a guilty verdict, handed down under the influence of the exciting and seductive speech by the prosecution. Others, however, differ from this perception, for pondering that the judgment rendered by common sense is more just and humane, and that citizens, when judging their fellow man, are exercising a portion of the state power, fruit of the democratic principle, present in the decision-making processes of the judiciary. Besides, the participation of the people would be a political issue to be considered, by allowing their peers to judge the defendant. On the other hand, it implies more security for the judge of law, who will not suffer retaliations from the accused, and for the jurors themselves, since the secrecy in the voting on who judged against or in favor of the proposed thesis will mean a guarantee of discretion for the judging body. To this end, the origin of this institution and of the participation of the people in the concept of justice was sought, and the complexity of the procedure related to crimes against life and the stratagems consistent with Arthur Schopenhauer's eristics, employed in the plenary session by the prosecution and the defense, with the objective of obtaining the winning account, will be brought to light. At the end, it will be explained that the jury court only has the status of a fundamental clause, which cannot be considered an obstacle to the abrogation of the institute, and the thesis will be exposed, based on the antitheses presented.